What can the Thinking and Working Politically community learn from pea ce and conflict mediation? - Douglas, Alex (2018)
Wily aid practitioners have long understood the importance of adapting their programs to the political environment, and even use their activ ities to push politics in a progressive direction. But this magic was spun secretly, hidden behind logframes and results frameworks. Only re cently has a range of programs been permitted to escape the dead hand of technocracy. But there was one corner of the development and humani tarian world that never needed to shroud its political ambitions; thos e of us working on resolving violent conflicts. Donors have always und erstood our work could never be disembodied from politics. This field included elements of the UN, regional organisations, and NGOs, such as the one I work for: the Centre for Humanitarian Dialogue. With a new focus on development being enabled by a series of ‘deals’ between diff erent actors, it seems timely to examine the strategies used to reach peace agreements and whether they contain broader lessons for TWP/DDD/ Adaptive Management.